Floristic composition of Serra da Fumaça, Northern Chapada Diamantina, Bahia, Brazil - Santos, Valdira de Jesus (2022)
The main objective of the present work was to carry out a floristic inventory of angiosperm species of the Serra da Fumaça, municipality of Pindobaçu, to increase knowledge of the flora and distribution patterns of species present in the northern Chapada Diamantina, Bahia, Brazil. To this aim, expeditions were carried out in the study area for a period of two years, in addition to a survey in the HUNEB and HUEFS herbaria. The fertile specimens were collected and processed following the usual botanical methods. Herborized material was identified and incorporated into HUNEB. A total of 217 species belonging to 52 botanical families were recorded, with an endemism index of 43.32% for Brazilian species, and 6.9% for Bahia. Rubiaceae, Orchidaceae, Fabaceae, Melastomataceae, Asteraceae, and Euphorbiaceae are among the most representative families in the study area, while the predominant type of habit was the herbaceous. The data presented here may support management plans with the purpose of conservation and preservation in the area, which is considered of extreme biological importance.